Transformasi Visual Branding: Peran Kecerdasan Buatan dalam Evolusi Desain Komunikasi Visual Kontemporer - Arus Reka Prasetia (Universitas Widyatama, 2026)
This research aims to analyze the transformation of visual branding through the role of artificial intelligence in the evolution of contemporary visual communication design. The method employed is a systematic literature review with a qualitative descriptive-analytical approach, analyzing 87 scientific publications from the 2019-2024 period obtained through Scopus, Web of Science, and Google Scholar databases. Data analysis techniques utilize qualitative content analysis with a thematic approach, encompassing coding, categorization, interpretation, and synthesis stages to identify transformation patterns in design practice and visual branding. Research findings reveal that artificial intelligence has transformed visual communication design in three fundamental dimensions: production efficiency that increases iteration speed by up to 300 percent, mass personalization enabling context-based visual adaptation to audiences, and creative exploration expanding aesthetic possibility spaces. The evolution of visual branding is characterized by a shift from static brand identities toward dynamic parametric systems, the emergence of paradoxes between automation and humanization needs, and ethical considerations regarding copyright and algorithmic bias. The designer's role has evolved from executor to strategic orchestrator with new competencies including prompt engineering, data interpretation, and curatorial skills. The research concludes that this transformation is not about human replacement by machines, but rather symbiotic collaboration where artificial intelligence amplifies human creative capabilities while preserving the fundamental values of visual communication design as a medium for meaning-making and meaningful emotional connections.